Connections between therapeutic circus arts and drama therapy: A qualitative content analysis of core processes. Issue 2 (1st October 2022) - Elowe, Rebecca; Schorr, Siggi; Faith, Emily; Alters, Brett; Wood, Laura L.
Therapeutic circus arts (TCA) present a new arena for drama therapy, capitalizing on the historical connection between circus and theatre arts. To evaluate whether drama therapy core processes also present in TCA, we conduct a qualitative content analysis of research articles centred on TCA (N = 40). Selected articles were thematically coded, showing that all of drama therapy's core processes also appear in the TCA literature. Of those processes, 'empathy and distancing', 'play', 'life-drama connection' and 'transformation' were especially prominent. Implications include the potential for knowledge sharing and future collaboration between the TCA and drama therapy fields.